Papież polonistów. Kilka uwag o antropologii literackiej, praktycznej retoryce i filologii polskiej w perspektywie myśli Jana Pawła II = Pope of specialists of Polish Literature. A few remarks on literal anthropology, practical rhetoric and Polish Literature in perspective of John Paul II`s thoughts - Heck, Dorota (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The pope, John Paul 2, was a former student of Polish philology in Cracow. He was a poet and play writer alluding to neoromantic style of Young Poland literature. He defended Polish tradition in the globalizing modern world. His literary anthropology and practical rhetoric were founded on this challenging tradition and on Latin civilization. Because of their deep metaphysical wisdom they are still inspiring for many literary critics students of Polish philology.
Keywords: Jan Paweł II, papież (1929-2005); John Paul II; antropologia literacka; retoryka; literal anthropology; rhetoric